Pengaruh Kecerdasan Emosional terhadap Motivasi Belajar Matematika Siswa Kelas IV SD Negeri 1 Ngulankulon - Fitriana As Sidik; Efi Ika Febriandari; Angga Setiawan (Bidayatuna, 2020)
This study aims to determine the level of emotional intelligence, find out the motivation to learn mathematics and determine the effect of emotional intelligence on motivation to learn mathematics. Using quantitative research with survey methods. Population and sample of all fourth grade students with 21 students. Data obtained by observation and disseminating the first questionnaire aims to find out emotional intelligence and the second questionnaire to determine student motivation. The research instrument uses a scale of emotional intelligence and motivation to learn mathematics. Descriptive analysis results show that the emotional intelligence of class IV students is in the medium category with a percentage of 14%, while the motivation to learn mathematics in class IV is in the moderate category with a percentage of 29%. After analyzing the data it is known that there is a significant influence with the results of r count = 16.991 and consulted with a value of t table = 1.729. While the influence of variable X (emotional intelligence) on the Y variable (mathematics learning motivation) was 93.8%. With these results, the alternative hypothesis is accepted and the null hypothesis is rejected. It can be concluded that there is a significant influence of the influence of emotional intelligence on mathematics learning motivation of fourth grade students of SD Negeri 1 Ngulankulon.